SARS‐CoV‐2 reinfection across a spectrum of immunological states. Issue 4 (22nd July 2022) - McKittrick, Justine M.; Burke, Thomas W.; Petzold, Elizabeth; Sempowski, Gregory D.; Denny, Thomas N.; Polage, Christopher R.; Tsalik, Ephraim L.; McClain, Micah T.
Abstract: Purpose: Several cases of symptomatic reinfection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) after full recovery from a prior episode have been reported. As reinfection has become an increasingly common phenomenon, an improved understanding of the risk factors for reinfection and the character and duration of the serological responses to infection and vaccination is critical for managing the coronavirus disease 2019 (COVID‐19) pandemic. Methods: We described four cases of SARS‐CoV‐2 reinfection in individuals representing a spectrum of healthy and immunocompromised states, including (1) a healthy 41‐year‐old pediatrician, (2) an immunocompromised 31‐year‐old with granulomatosis with polyangiitis, (3) a healthy 26‐year‐old pregnant woman, and (4) a 50‐year‐old with hypertension and hyperlipidemia. We performed confirmatory quantitative reverse transcription‐polymerase chain reaction and qualitative immunoglobulin M and quantitative IgG testing on all available patient samples to confirm the presence of infection and serological response to infection. Results: Our analysis showed that patients 1 and 2, a healthy and an immunocompromised patient, both failed to mount a robust serologic response to the initial infection. In contrast, patients 3 and 4, with minimal comorbid disease, both mounted a strong serological response to their initial infection, but were still susceptible to reinfection. Conclusion: Repeat episodes of COVID‐19 are capable of occurring in patients regardless of the presence of known risk factors for infection or level of serological response to infection, although this did not trigger critical illness in any instance.